Improving Maternal Representations in High-Risk Mothers: A Randomized, Controlled Trial of the Mom Power Parenting Intervention. - Rosenblum, Katherine; Lawler, Jamie; Alfafara, Emily; Miller, Nicole; Schuster, Melisa; Muzik, Maria (Child Psychiatry & Human Development, 2018)
A key mechanism of risk transmission between maternal risk and child outcomes are the mother's representations. The current study examined the effects of an attachment-based, trauma-informed parenting intervention, the Mom Power (MP) program, in optimizing maternal representations of high-risk mothers utilizing a randomized, controlled trial design (NCT01554215). High-risk mothers were recruited from low-income community locations and randomized to either the MP Intervention (n = 42) or a control condition (n = 33) in a parallel design. Maternal representations were assessed before and after the intervention using the Working Model of the Child Interview. The proportion of women with balanced (secure) representations increased in the MP group but not in the control group. Parenting Reflectivity for mothers in the treatment group significantly increased, with no change in the control condition. Participation in the MP program was associated with improvements in a key indicator of the security of the parent-child relationship: mothers' representations of their children.